2015
DOI: 10.5463/dcid.v26i3.456
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Games as an Intervention for Children: A Pilot Study

Abstract: Purpose: This pilot study explored the use of virtual reality-based games as an enjoyable yet effective intervention to improve skills in children with developmental disabilities. Although the intervention was primarily targeted at the enhancement of motor skills, the children’s communication, cognitive and social/emotional skills were also monitored and changes, if any, were tracked during this period.Methods: Therapists guided 5 children (4 boys with Autism Spectrum Disorder and 1 girl with Learning Disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…A post hoc power analysis showed very large effect sizes and thus large power for DASH-2 measurements in the small experimental group. Similar results of a positive influence of educational games on motor skills in participants with ASD were previously presented by Muneer, Saxena, and Karanth (2015) over one month of playing Kinect games, also involving five students with ASD. As sessions were held, participants completed the educational games in shorter times, indicating that they became more skilled in choosing and combining strategies for completing the task during these game-playing training sessions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A post hoc power analysis showed very large effect sizes and thus large power for DASH-2 measurements in the small experimental group. Similar results of a positive influence of educational games on motor skills in participants with ASD were previously presented by Muneer, Saxena, and Karanth (2015) over one month of playing Kinect games, also involving five students with ASD. As sessions were held, participants completed the educational games in shorter times, indicating that they became more skilled in choosing and combining strategies for completing the task during these game-playing training sessions.…”
Section: Discussionsupporting
confidence: 82%
“…A post hoc power analysis showed very large effect sizes and thus large power for DASH-2 measurements in the small experimental group. Similar results of a positive influence of educational games on motor skills in participants with ASD were previously presented by Muneer, Saxena, and Karanth (2015) over one month of playing Kinect games, also involving five students with ASD.…”
Section: Discussionsupporting
confidence: 82%
“…The total sample of the four studies that evaluated motor imitation comprised 61 participants (47 male) aged between 3 and 13 years (Ganz et al, 2008; Muneer et al, 2015; Schwartz et al, 2004; Stephens, 2008); with the majority of these participants coming from one study of 48 children (Schwartz et al, 2004). Three of the samples, including Schwartz et al (2004), included participants with a diagnosis of an ASD (Ganz et al, 2008; Muneer et al, 2015), one of which included one participant who did not have a diagnosis of ASD but instead was described as having a learning disability (Muneer et al, 2015). This sample is included as the majority of these participants had received a diagnosis of an ASD.…”
Section: Resultsmentioning
confidence: 99%
“…One article specified that the motor imitation measured was based on object-action (Ganz et al, 2008). Three articles reported imitation based on the frequency of this behavior: Two articles reported the frequency of motor imitation (Ganz et al, 2008; Stephens, 2008), and one article reported the frequency of motor imitation with consideration to consistency and reduced reliance on prompts (Muneer et al, 2015). Schwartz et al (2004) reported the percentage of participants who presented motor imitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation